Correlations between plasma homocysteine and MTHFR gene polymorphism and white matter lesions - Li, Min; Fu, Bing; Dong, Wanli (Folia Neuropathologica, 2018)
This study aims to investigate the correlation between the plasma homocysteine (Hcy) level and methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism, and white matter lesions (WML). The plasma Hcy level and MTHFR C677T gene polymorphism in 104 patients with white matter lesions and 74 controls were measured. The severity of cerebral white matter was scored on the magnetic resonance imaging (MRI) images by the modified Scheltens scale (score of 0-30). The plasma Hcy level in the WML group was remarkably higher than that in the control group (p < 0.05), and the proportion of the patients with a high Hcy level in the WML group was notably higher than that in the control group (p < 0.05). Moreover, the patients with TT genotype in MTHFR gene had a significantly higher plasma Hcy level than those with CT or CC genotype. In addition, the plasma Hcy level in the patients with CT genotype was also significantly different from that in the patients with CC genotype (p 0.05). The plasma Hcy level is positively correlated with WML and significantly correlated with C677T gene polymorphism in MTHFR gene. The severity of white matter lesions is not correlated with MTHFR C677T gene polymorphism.